A Mendelian randomization study of the gut microbiota and risk of knee osteoarthritis and the mediating role of immune cells - Jiayu Zhang; Xiuyue Qiu (Scientific Reports)
Abstract With increasing research on the gut microbiota (GM), there is growing evidence suggesting that GM may influence the risk of knee osteoarthritis (KOA) by modulating immune cell activity. However, the causal relationship between GM, immune cells, and KOA has not been thoroughly investigated. This study aimed to investigate the causal effect of GM on KOA and to identify immune cell mechanisms that may play a mediating role. A bidirectional two-sample univariable Mendelian randomization (UVMR) analysis was conducted to assess the association between GM and KOA. Additionally, mediation analyses were performed to identify critical mediators in the association between GM and KOA, assessing the causal relationship between the two conditions and potential immune cell mediators. UVMR analyses revealed a causal relationship between 20 GM and KOA. Reverse MR analysis revealed that KOA affected the abundance of 12 GM. Mediation analysis identified that CCR7 on naive CD4+, CD4+ on CD39+ activated Tregs mediated the causal effect of GM on KOA (indirect effect: β = 0.049; indirect effect: β =  − 0.047). Furthermore, GM was found to be a significant contributor to the risk of KOA. Specifically, Firmicutes A was associated with increased risk of KOA by increasing CCR7 on naive CD4+ (OR = 1.480; P = 0.006; FDR = 0.039). In contrast, Rhodanobacter was protective against KOA by modulating CD4+ on CD39+ activated Tregs (OR = 0.780; P = 0.046; FDR = 0.048). These findings provide a rationale for potential new prevention strategies for KOA.